Deterioration mechanism of loess from Ili valley region of China under wet and dry cycles: evidences from shear tests - Lai, Runsen; Zhang, Zizhao; Zhang, Yanyang; Chen, Debin; Shi, Guangming; Fu, Qiang (Frontiers in Earth Science, 2023)
The properties of loess in the Ili region of China are significantly affected by repeated cycles of rainfall and evaporation. It is thus essential to investigate the deterioration mechanism of loess subjected to the wet and dry cycles. This paper employs various methods, including the direct shear and triaxial shear tests, as well as the scanning electron microscopy (SEM), to evaluate the variation patterns of shear strength parameters and microstructure of Ili loess. The direct shear test was conducted on loess samples experiencing a limited number of wet and dry cycles (0, 1, 3, 5, 7, and 9), while the triaxial shear test focused on a more extensive range of wet and dry cycles (0, 1, 3, 10, 20, and 30). In parallel, the alterations in the shear strength parameters of the loess material under different shear tests were also scrutinized. The findings obtained from this research revealed that the shear strength of Ili loess decreased to varying degrees based on the two test methods when they are affected by the wet and dry cycles. Comparing the results with the same number of wet and dry times (0, 1 and 3 times), both the shear strength and cohesion obtained from the triaxial shear test were greater than those from the direct shear test, while the results for the angle of internal friction were reversed. Moreover, the scanning electron microscope tests on Ili loess did indicate that the microparticle size, pore space, morphology, soil structure, and particle contact mode exhibited the deterioration with different degrees. The micro-structural change is believed to be the main reason for the deterioration mechanism of the shear strength. The research outcomes will enrich the understanding about the loess properties in Central Asia, providing data reference and theoretical basis for engineering construction in these region.